Approving the ISDWIR method of risk measurement in making risk management decision - Mikhail Strelnik (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2014)
This paper is devoted to risk management and risk measurement methods. The author considers methods of risk measurement and proposes the Inte- gral Sum of Differential Weighted Indexes of Risks (or ISDWIR) method of risk measurement. The method is based on dynamic enterprise risk matri- ces. The matrix describes the changes of corporate risk values over the time. The method assists to choose risk management decision having good effects on corporate risk values. The ISDWIR method is also compared with other risk measurement methods.
Keywords: M10; 330; uncertainty; risk; risk management; risk measurement; matrix